Water resources management in Sperchios River Basin, using SWOT analysis - Stathopoulos, N.; Rozos, D.; Vasileiou, E. (Bulletin of the Geological Society of Greece, 2013)
SWOT (Strengths, Weaknesses, Opportunities and Threats) analysis is a useful tool for sustainable development and decision making about environmental planning and water resources management. This analysis was applied in order to evaluate the water resources of the wider area of Sperchios River. Sperchios River basin, with an average altitude of approximately 810m, covers an area of 2116 km2. The river is recharged by many streams of permanent and periodic flow and discharges in Maliakos Gulf. The steep slopes, which are present within approximately 2/3 of the total length of the river course, form a rather mountainous topography (streamy, with crucial flooding peaks and very intense sediment yield). Only in the last downstream part of Sperchios course, the topography gradually changes into a lowland relief, with an extent at the river mouth of 1830 km2. At this part of Sperchios severe cases of flooding have been occasionally observed and reported. Regarding the SWOT applications on the wider area of Sperchios River, various data were processed (geological, meteorological, hydrological, hydrogeological, land use, socio-economic and environmental parameters) in order to suggest a water management planning in the area.